I-invertebrata as an android-based learning media for molluscs, arthropods, and echinoderms identification and its influence on students motivation - Widiansyah, Arindra Trisna; Indriwati, Sri Endah; Munzil, Munzil; Fauzi, Ahmad (University of Muhammadiyah Malang, 2018)
In Zoology course, students often have difficulty to identify several invertebrates. Android-based learning media is currently an alternative way of solving some problems during the learning process. Therefore, android-based learning media that assist students to identify invertebrates was developed in this study. This research method used to research and development model (R&D) developed by Borg and Gall (1983) that consisting 10 steps, that are research and data collection; planning the educational product; developing the products preliminary form; initial field testing; the first revision of main product; main field testing; operational product revision; operational field testing; final product revision; and dissemination. The validation results from the material expert I, material expert II, and media experts were 96.6%; 94.3%; and 94.7%, respectively. Â That results concluded I-Invertebrata was feasible for use in learning but requires minor revision. Furthermore, the results of quasi-experimental research that was analyzed by using analysis of covariance test showed the learning motivation of students who use I-Invertebrata is significantly higher than students who do not use I-Invertebrata.